2018
DOI: 10.1161/jaha.118.010069
|View full text |Cite
|
Sign up to set email alerts
|

VPO1 Modulates Vascular Smooth Muscle Cell Phenotypic Switch by Activating Extracellular Signal‐regulated Kinase 1/2 (ERK 1/2) in Abdominal Aortic Aneurysms

Abstract: BackgroundHydrogen peroxide (H2O2) is a critical molecular signal in the development of abdominal aortic aneurysm (AAA) formation. Vascular peroxidase 1 (VPO1) catalyzes the production of hypochlorous acid (HOCl) from H2O2 and significantly enhances oxidative stress. The switch from a contractile phenotype to a synthetic one in vascular smooth muscle cells (VSMCs) is driven by reactive oxygen species and is recognized as an early and important event in AAA formation. This study aims to determine if VPO1 plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 39 publications
(46 reference statements)
1
42
1
Order By: Relevance
“…Cd, which binds to intracellular SH‐groups or may favor Fenton reaction by increasing free Fe 2+ , may indirectly induce oxidative stress, at least redox imbalance, and a positive correlation between ERK1/2 activation and pro‐oxidant conditions (related to H 2 O 2 ) have been shown in many studies . Our data show higher levels of Cd‐induced ERK1/2 phosphorylation in the presence of 3 mM BSO but lower levels when the cells were coincubated with Cd and 1 mM NAC (Figure ).…”
Section: Resultssupporting
confidence: 72%
“…Cd, which binds to intracellular SH‐groups or may favor Fenton reaction by increasing free Fe 2+ , may indirectly induce oxidative stress, at least redox imbalance, and a positive correlation between ERK1/2 activation and pro‐oxidant conditions (related to H 2 O 2 ) have been shown in many studies . Our data show higher levels of Cd‐induced ERK1/2 phosphorylation in the presence of 3 mM BSO but lower levels when the cells were coincubated with Cd and 1 mM NAC (Figure ).…”
Section: Resultssupporting
confidence: 72%
“…Since GSK-3β has been demonstrated to directly phosphorylate KLF5 at S303 and then targets it for ubiquitination and degradation (43), suggesting that FTO upregulates Klf5 expression at protein level via inactivation of GSK-3β inhibits its phosphorylation and degradation. Additionally, previous reports show that PI3K/AKT signaling pathway mediates FTO-induced the energy metabolism of breast cancer cell (44), and proliferation-related ERK signaling pathway is activated heavily in aneurysms (45), however, in this study, we found that overexpression of FTO has little effects on these two signaling pathways in VSMCs. These findings indicate that FTO correlates with the distinct signaling pathways in the different cell contexts and particular pathways to exert corresponding functions.…”
Section: Forced Expression Of Fto Promotes the Proliferation Andcontrasting
confidence: 82%
“…Consistent with that idea, alteration of the VSMC phenotype reportedly contributes to aortic aneurysm formation or dissection in MFS [1, 18]. It has been reported that VPO1 promotes VSMC phenotypic switching through activation of the HOCl/ERK1/2 signaling pathway with consequent development of aortic aneurysm [19]. The XBP1u-FoxO4-myocardin axis is essential for maintaining the VSMC phenotype and blocking signaling leading to VSMC phenotypic transition [20].…”
Section: Discussionmentioning
confidence: 77%